Preliminary Findings on a Newly Developed Malaysian Multilingual Sentence Repetition Task for Multilingual Chinese Children in Malaysia - Razak, Rogayah Bt; Cho, Cho Kai Shuo; Abu Bakar, Norsofiah Abu Bakar (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Even though multilingualism is the basic fabric of linguistic diversity of mainstream communities in Malaysia, there is generally a lack of assessment tool to assess the language abilities of multilingual children at risk of language impairment. This study is aimed at developing a Malaysian Multilingual Sentence Repetition (MMSR) task which can be used to assess the morphosyntactic abilities of multilingual Chinese children speaking three languages i.e., English-Mandarin-Malay. MATERIALS AND METHOD: 10 typically developing Chinese children within the ages of 4 years until 6 years and 11 months old were recruited. Each child was presented with sentences auditorily using a laptop with a microphone headset. The child was then asked to repeat verbatim the sentences they just heard. RESULTS: Findings showed that the subjects performed equally well in English and Mandarin but lower in Malay (p < 0.01). Correlation analyses revealed that the older children performed better for English (p < 0.05) and Mandarin (p < 0.01) sentence repetitions (SRs). Performance on SR tasks decreased with the increase in sentence length and complexity. CONCLUSION: The newly developed multilingual SR task proved reliable and valid as a tool and has the potential to be developed into a standardized test to assess multilingual Malaysian children at risk of language impairment.